2015
DOI: 10.5194/bg-12-2347-2015
|View full text |Cite
|
Sign up to set email alerts
|

Glacial meltwater and primary production are drivers of strong CO<sub>2</sub> uptake in fjord and coastal waters adjacent to the Greenland Ice Sheet

Abstract: Abstract. The Greenland Ice Sheet releases large amounts of freshwater, which strongly influences the physical and chemical properties of the adjacent fjord systems and continental shelves. Glacial meltwater input is predicted to strongly increase in the future, but the impact of meltwater on the carbonate dynamics of these productive coastal systems remains largely unquantified. Here we present seasonal observations of the carbonate system over the year 2013 in the surface waters of a west Greenland fjord (Go… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
166
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(180 citation statements)
references
References 44 publications
13
166
1
Order By: Relevance
“…8c and d), for example, has nearly constant DIC throughout the year, while TA drops to less than half of the DIC concentration at peak river discharge (Wang et al, 2013). Another exception is cold glacial meltwater (magenta square), which, even at a DIC : TA more than twice as high as our High Carbon scenario, is pCO 2 -undersaturated relative to the atmosphere and continues to take up DIC as it mixes with seawater (Meire et al, 2015). Seasonal biological productivity may also regulate DIC in some temperate rivers, at least near the river mouth, as it does in the Fraser River.…”
Section: Comparison To Other Rivers and Implications For Future Climatementioning
confidence: 75%
See 1 more Smart Citation
“…8c and d), for example, has nearly constant DIC throughout the year, while TA drops to less than half of the DIC concentration at peak river discharge (Wang et al, 2013). Another exception is cold glacial meltwater (magenta square), which, even at a DIC : TA more than twice as high as our High Carbon scenario, is pCO 2 -undersaturated relative to the atmosphere and continues to take up DIC as it mixes with seawater (Meire et al, 2015). Seasonal biological productivity may also regulate DIC in some temperate rivers, at least near the river mouth, as it does in the Fraser River.…”
Section: Comparison To Other Rivers and Implications For Future Climatementioning
confidence: 75%
“…For example, the relatively high DIC : TA ratio of the present-day glacial DIC and TA endmember (magenta square, Fig. 8c, d) is in equilibrium with the atmosphere at a river temperature of 0 • C (Meire et al, 2015), but if this pure glacier water were to experience a 10 • C increase during its passage to the ocean, then outgassing would decrease river DIC by about 10 % (∼ 9 µmol kg −1 ) if the meltwater remained in atmospheric equilibrium. However, its pH would stay about the same (slight increase) in this scenario.…”
Section: Comparison To Other Rivers and Implications For Future Climatementioning
confidence: 99%
“…With increasing surface air temperatures over the Arctic, recent increases in annual mass loss from the Greenland Ice Sheet (van Angelen et al, 2013;Vizcaíno et al, 2014) are expected to continue. Fjords in Greenland are important both as carbon sinks (Rysgaard et al, 2012;Sejr et al, 2014;Meire et al, 2015) and as distinct components of the coastal ecosystem (Tang et al, 2011;Arendt et al, 2013;Dziallas et al, 2013). Seasonal discharge from the Greenland Ice Sheet creates strong lateral and vertical gradients in the physical properties of water along these fjords (Rysgaard et al, 2003;Mortensen et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…While the remineralization of highly labile DOC between station occupations could have added DIC back into mixed layer and decreased the signal of seasonal drawdown, any significant contribution of DIC from remineralization in the mixed layer seems unlikely given the slow remineralization rates and the short time periods (∼ 30 days) between station occupations. Additionally, while glacial freshwater input has been shown to have some impact on NCP estimates in Greenland fjords, Meire et al (2015) found biological processes to be the main driver of carbon dynamics. In a study similar to ours in Glacier Bay, Alaska, Meire and his team estimated air-sea CO 2 fluxes and NCP in the Godthåbsfjord system in western Greenland, as well as the impact of freshwater on these estimates.…”
Section: Caveatsmentioning
confidence: 97%
“…In a study similar to ours in Glacier Bay, Alaska, Meire and his team estimated air-sea CO 2 fluxes and NCP in the Godthåbsfjord system in western Greenland, as well as the impact of freshwater on these estimates. They identified biological processes as the most important driver of carbon dynamics, accounting for 65 to 70 % of the total CO 2 uptake by the fjord system (Meire et al, 2015).…”
Section: Caveatsmentioning
confidence: 99%